Maple samaras recover autorotation following raindrop collisions - Breanna M. Schaeffer; Tadd T. Truscott; Andrew K. Dickerson (Proceedings of the National Academy of Sciences, 2025)
Samaras are known for their elegant and robust autorotation, a resilience that persists in the adverse conditions imposed by high-speed raindrops. Like flying insects, samaras descending from tall trees are likely to be struck by raindrops in an intense storm. In this study, we detail the collision dynamics for impact regions across the samara body and the drop-shedding mechanisms that samaras exhibit to return to autorotation. Impacts across the samara body can pitch the samara up to 60 degrees and, in some cases, induce spanwise roll. Raindrops may shatter or remain intact upon impact, pushing the undamaged samara downward before autorotation is recovered. Drops that strike near the wingtip elicit the greatest recovery distance, while impacts onto the nutlet mass are the least disruptive to the samara and most likely to cause the drop to induce fragmentation. Faster drops allow for quicker drop shedding and a subsequent rapid return to autorotation in less than 50 ms. Our results indicate that samaras are robust to raindrop impacts and consistently recover autorotation, resulting in a minor reduction in dispersal distance. To recover, the entire drop is shed from the spinning samara over a time closely tied to the shedding mode and ensuing drop rejection forces.